The use of mechano growth factor to prevent cartilage degeneration in knee osteoarthritis. (6th October 2017) - Song, Yang; Xu, Kang; Yu, Can; Dong, Lili; Chen, Peixing; Lv, Yonggang; Chiang, Martin Y.M.; Li, Linhao; Liu, Wanqian; Yang, Li
Abstract: Previous studies have attached more importance to growth factors in treating cartilage degeneration and osteoarthritis (OA). Here, the capability of mechano growth factor‐C24E (MGF) to prevent osteoarthritic cartilage degeneration was evaluated in vitro and in vivo. Using in vitro cultured human OA chondrocytes treated with 10–60‐ng/ml MGF for 12 hr, we detected the cell proliferation, migration, and anabolism of OA chondrocytes. The unfolded protein response and the protein characteristic of OA pathology, such as transforming growth factor β, SMAD family member 3, and hypoxia‐inducible factor 2α of OA chondrocytes, were also detected by western blotting. Furthermore, protein kinase RNA‐like endoplasmic reticulum kinase was knocked down via small interfering RNA to illuminate the potential mechanism of MGF's treatment of OA. In a rabbit knee joint OA model, cartilage degeneration was inhibited after 2 weeks of treatment with 0.1–10‐μg/ml MGF. This study demonstrated that MGF treatment can inhibit the pathological apoptosis of OA chondrocytes and promote the proliferation, migration, and matrix synthesis of the chondrocytes. The results also demonstrate that the degeneration of OA cartilage can be delayed by MGF treatment partially via unfolded protein response regulated by protein kinase RNA‐like endoplasmic reticulum kinase and suggest a potential therapeutic application of MGF for OA treatment.